Structural basis for TNA synthesis by an engineered TNA polymerase - Nicholas Chim (Nature Portfolio, 2017)
The laboratory-evolved polymerase Kod-RI catalyzes α-L-threose nucleic acid (TNA) synthesis. Here, the authors present Kod-RI crystal structures that give insights into how TNA triphosphates are selected and extended in a template-dependent manner, which will help to engineer improved TNA polymerases for synthetic genetics applications.